Increased pre-diabetic blood glucose levels as a risk factor of elevated systolic, but not diastolic, arterial pressure - Tadla, Monika; Skolarczyk, Justyna Magdalena; Pekar, Joanna; Olszewska, Anna; Skórzyńska-Dziduszko, Katarzyna (Journal of Education, Health and Sport, 2017)
Introduction. The Finnish Diabetes Risk Score (FINDRISC) assesses the 10-year type 2 diabetes risk in adults by identifying individuals with overweight or obesity, inadequate physical activity, poor nutrition, or a family or personal history of hyperglycemia. Aim. The objective of the study was to analyze the effect of personal history of increased (pre-diabetic) venous blood glucose on body weight, waist circumference, the magnitude of arterial pressure, and the total FINDRISC score of randomly selected individuals. Materials and methods. The study was conducted in years 2015/2016 on 190 individuals – 96 women and 94 men. We determined FINDRISC score and measured blood pressure twice. The results were analyzed in STATISTICA 10 at p < 0.05. Results. Interestingly, subjects with personal history of increased blood glucose had significantly higher systolic blood pressure (p=0.03), but not diastolic blood pressure, than subjects with history of normoglycemia. Both waist circumference (p=0.01) and total FINDRISC scores (p<0.001) were significantly elevated in the first group. Subjects with personal history of increased venous blood glucose showed a strong tendency (p = 0.055) towards higher body mass index (BMI) values than subjects with history of normoglycemia. Discussion. Cardiovascular autonomic dysfunction(CAD) seems to be a main reason for hypertension in early stages of glucose dysmetabolism. Conclusion. Increased pre-diabetic blood glucose level is an important risk factor of elevated systolic pressure, whereas diastolic pressure seems to be not affected by this factor.